KRITERIA MANAJEMEN PELAYANAN PADA PENYUSUNAN PROGRAM KERJA DI BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN MINAHASA UTARA - FREDERIK, ADRIEL JUAN; Posumah, Johnny Hanny; Kolondam, Helly (Sam Ratulangi University, 2017)
Abstract : In carrying out the service management criteria there are also various complicated matters,such as in government agencies, especially the unity of the nation and politics are also inseparable fromthe various problems that convolve I. Judging from the reality of some problems such is not beingconsidered the criteria of service management to the planning in the preparation of work programs,such us professionalism and skill, attitudes and behavior, accessibility and flexibility, reability andtrustworthiness, recovery, reputation credibilityRresearch by as much as 10 (ten) informant: 1 person head of department, 1 secretary, 1 head of sub.Planning, 1 head of sub. General, 6 civil state apparatus. Data collection techniques used are interview,observation, and documentation. As well as data analysis techniques used are data reduction,presentation, and conclusion.Keyword : Service Management Criteria, Work Program